Weld quality and dynamic corrosion behavior of ship pipeline systems - Zhiwei Guo; Sheng Hu; Dingjia Bai; Pan Jiang (AIP Advances)
Three types of specimens (defect-free, with porosity defects, and with slag inclusions) were prepared via manual arc welding of Q355 steel. The effects of welding defects on the dynamic corrosion of ship pipeline systems under different conditions were revealed through macroscopic morphology, surface roughness test, atomic absorption spectroscopy test, microscopic morphology, and x-ray diffractometer detection of corrosion products. As the Cl− concentration increased, the color of the rust layer around the weld darkened, and uneven protrusions accumulated. The corrosion products are γ-FeOOH, α-FeOOH, and Fe3O4. Welding defects enhance the stratification of the rust layer and lead to more serious corrosion. Both the weld zone (WZ) and the heat-affected zone (HAZ) started from the corrosion pit and expanded, ultimately reaching into the flake corrosion zone. The degree of corrosion in the WZ was more severe than in the HAZ. The degrees of corrosion in the WZ and the HAZ of the sample with porosity defects were higher than those of the sample with slag inclusions, and the sample without defects exhibited the least corrosion.